How to decide adequately? Qualitative study of GPs' view on decision-making in self-referred and physician-referred emergency department consultations in Berlin, Germany. Issue 4 (2nd April 2019) - Oslislo, Sarah; Heintze, Christoph; Schmiedhofer, Martina; Möckel, Martin; Schenk, Liane; Holzinger, Felix
Abstract : Objectives: Patients with acute symptoms present not only to general practitioners (GPs), but also frequently to emergency departments (EDs). Patients' decision processes leading up to an ED self-referral are complex and supposed to result from a multitude of determinants. While they are key providers in primary care, little is known about GPs' perception of such patients. This qualitative study explores the GPs' view regarding motives and competences of patients self-referring to EDs, and also GPs' rationale for or against physician-initiated ED referrals. Design: Qualitative study with semi-structured, face-to-face interviews; qualitative content analysis. Setting: GP practices in Berlin, Germany. Participants: 15 GPs (female/male: 9/6; mean age 53.6 years). Results: The interviewed GPs related a wide spectrum of factors potentially influencing their patients' decision to visit an ED, and also their own decision-making in potential referrals. Considerations go beyond medical urgency. Statements concerning patients' surmised rationale corresponded to GPs' reasoning in a variety of important areas. For one thing, the timely availability of an extended spectrum of diagnostic and therapeutic options may make ED services attractive to both. Access difficulties in the ambulatory setting were mentioned as additional triggers for an ED visit initiated by a patient or a GP. Key patient factors like severity of symptoms and anxiety also play a major role; a desire for reassurance may lead to both self-referred and physician-initiated ED visits. Patients' health competence was prevailingly depicted as limited, with the internet as an important influencing factor. Counselling efforts by GP were described as crucial for improving health literacy. Conclusions: Health education could hold promise when aiming to reduce non-urgent ED consultations. Primary care providers are in a key position here. Amelioration of organisational shortages in ambulatory care, for example, limited consultation hours, might also make an important impact, as these trigger both self-referrals and GP-initiated ED referrals. Trial registration number: DRKS00011930.